Continuous Phosphate Removal and Recovery Using a Calcium Silicate Hydrate Composite Monolithic Cryogel Column - Phawachalotorn, Chanadda; Wongniramaikul, Worawit; Taweekarn, Tarawee; Kleangklao, Bussakorn; Pisitaro, Wachiraporn; Limsakul, Wadcharawadee; Sriprom, Wilasinee; Towanlong, Wanchitra; Choodum, Aree (My University, 2023)
Toward the development of a practical and green approach for removing phosphate from water, a monolithic cryogel based on starch and calcium silicate hydrate (Cry–CSH) was employed as a phosphate adsorbent in a continuous flow system for the first time. The influence of flow rate, initial phosphate concentration, and adsorbent height on the adsorption efficiency was investigated. As the rate of flow and the initial concentration of phosphate increased, the total quantity of adsorbed phosphate dropped; however, the performance of the column was greatly enhanced by an increase in adsorbent height. The experimental data fit the Adams–Bohart model better than the Thomas and Yoon–Nelson models at the beginning of the adsorption process. To evaluate its applicability, the continuous flow system based on the monolithic Cry–CSH column was applied for the removal of phosphate from the discharge effluent of the Patong Municipality Wastewater Treatment Plant (Phuket, Thailand), achieving an excellent total adsorption of 94.61%.
Keywords: calcium silicate hydrate; continuous flow adsorption; phosphate removal; starch cryogel